Концепция проекта федерального закона «О федеральной контрактной системе» - Головщинский, Константин; Шамрин, Александр (Вопросы государственного и муниципального управления, 2011)
The article discusses the problem of legislation development in the sphere of public procurement. Th ere is a general description and assessment of the existing legal regulations given in the article, as well as creating ideas and setting goals of the federal contracting system. It describes examples from the international practice.